2018
DOI: 10.1186/s40359-017-0211-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring narratives of resilience among seven males living with spinal cord injury: a qualitative study

Abstract: BackgroundIt is a challenge for both individuals and families when an illness or traumatic injury results in a severe spinal cord injury. The on-going physical impairments experienced by persons with spinal cord injury play themselves out over time. Few qualitative studies have explored how health, resilience and wellbeing interplay across time among persons living with the consequences of severe physical injuries. Thus, the aim of this study was to obtain a deeper understanding of how individuals with spinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 40 publications
4
50
0
4
Order By: Relevance
“…The anxiety symptomatology in this group of caregivers was positively associated with depression and caregiver burden and was negatively associated with quality of life, negative coping, family support, and social support networks. These results coincide with previous empirical findings [1, 2, 4, 11, 13, 14, 21, 24, 34, 35, 37, 39]. Furthermore, the regression model indicated that depression, a heavy caregiver burden, low emotional well-being, low self-esteem, and a negative coping style helped predict the presence of anxiety in family caregivers.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The anxiety symptomatology in this group of caregivers was positively associated with depression and caregiver burden and was negatively associated with quality of life, negative coping, family support, and social support networks. These results coincide with previous empirical findings [1, 2, 4, 11, 13, 14, 21, 24, 34, 35, 37, 39]. Furthermore, the regression model indicated that depression, a heavy caregiver burden, low emotional well-being, low self-esteem, and a negative coping style helped predict the presence of anxiety in family caregivers.…”
Section: Discussionsupporting
confidence: 90%
“…Participants responded in writing to A Sociodemographic Variables Questionnaire (Q-SV) that was developed for research on family caregivers of children with chronic diseases [24]. This instrument is composed of 20 items that measure individual, familial, and caregiver factors, such as age, sex, and marital status.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Social support: Oslothree-item social support scale, it is a three-item questionnaire, the sum score scale ranging from 3–14, which has three categories: poor support 3–8, moderate support 9–11 and strong support 12–14. 11 …”
Section: Methodsmentioning
confidence: 99%
“…A Sociodemographic Variables Questionnaire (Q-SV) for research on family caregivers of children with chronic diseases [49]. This instrument is composed of 20 items that measure individual, familial, and caregiver factors such as age, gender, and marital status.…”
Section: Methodsmentioning
confidence: 99%